2004
DOI: 10.1023/b:bege.0000017869.30151.fd
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Basis of Problem Behavior in 5-Year-Old Dutch Twin Pairs

Abstract: Different instruments can be used in the assessment of psychopathology in young children. In the present study the psychometric properties of a subset of items of the Devereux Child Behavior (DCB) rating scale were evaluated and the contribution of genetic and environmental influences to the variance of derived problem behavior scales was estimated. Maternal and paternal ratings were obtained in about 7600 5-year-old Dutch twin pairs. Six problem scales were derived from exploratory and confirmatory factor ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Twins' zygosity was assigned by the parent-rated Goldsmith questionnaire [21], which has an accuracy of determination of 99.4% [54]; according to its algorithm, there were 74 monozygotic (MZ) males, 70 MZ females, 134 same-sex dizygotic (DZS, 53 males, 81 females), and 120 different sex dizygotic (DZU) twin pairs. The zygosity of these 398 pairs was not different from that of the larger ITR population, and the MZ/DZS/DZU ratio was 1.1/1.0/0.9.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twins' zygosity was assigned by the parent-rated Goldsmith questionnaire [21], which has an accuracy of determination of 99.4% [54]; according to its algorithm, there were 74 monozygotic (MZ) males, 70 MZ females, 134 same-sex dizygotic (DZS, 53 males, 81 females), and 120 different sex dizygotic (DZU) twin pairs. The zygosity of these 398 pairs was not different from that of the larger ITR population, and the MZ/DZS/DZU ratio was 1.1/1.0/0.9.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional scales of the CBCL have been used in a number of behavioural genetic studies in order to provide insight on the magnitude of genetic and environmental influences on psychopathology in childhood [6,25,36,42,54]. Recently, we have examined the aetiological influences on the CBCL DOS as defined by Achenbach and Rescorla [2] in twins belonging to the Italian Registry by quantitative ML approach; our results show that the phenotypic variance of the new DOS scales is explained by only additive genetic and unique environmental agents.…”
Section: Introductionmentioning
confidence: 99%
“…Internalizing and externalizing broad band scales were used with the CBCL data, and seven specific problem scales were used for the DCB data. The CBCL age 2/3 is described by Derks et al (2004) and the derived problem scales of the DCB are described by Van Beijsterveldt et al (2004).…”
Section: Analysesmentioning
confidence: 99%
“…Using the Devereux Child Behavior Rating Scale (DCB; Spivack & Spotts, 1966) in a sample of 8041 5-year-old twin pairs, Van Beijsterveldt et al (2004) reported heritabilities of 50 to 80% for maternal ratings of aggression, anxiety, dependency, emotional lability and attention problems.…”
mentioning
confidence: 99%
“…Twin studies [19][20][21][22][23] have suggested that additional genetic efects account for a small portion of variance in children's trait anxiety and depression compared to non-shared environment (i.e. non-parenting factors).…”
Section: Introductionmentioning
confidence: 99%